Influence of CNT Incorporation on the Carbonation of Conductive Cement Mortar - Gun-Cheol Lee (MDPI AG, 2021)
This study analyzed the influence of carbon nanotubes (CNTs) on the carbonation conductive cementitious composites. Two powder types of CNT, multi-walled and single-wall CNTs, were employed to give the cement mortar the conductivity, and four tests including the accelerated carbonation, compressive and flexural strength, electrical resistance, and porosity tests were carried out. To intentionally accelerate the carbonation, the prismatic specimens of conductive cement composites were fabricated and stored in the controlled environmental chamber at a constant temperature of 20 ± 2 °C, constant relative humidity of 60 ± 5%, and carbon dioxide (CO2) concentration of 5% for 12 weeks. It was observed that carbonation resulted in only chemical damage so that there was no change in the electrical resistance value of conductive cementitious mortar that had undergone a carbonation attack.